Linkages among Soil Fertilization Regimes, Chemical Properties and Maize Grains Yield in Humid Tropic (Research, Society and Development, 2021)
We hypothesize that there is a linkage among different soil fertilization regimes, soil chemical attributes and maize grains yield. We aimed to evaluate the relationships between different soil fertilization regimes, soil chemical properties and maize grains yield. The experiment was performed in northeastern Brazil, in a randomized block design, at an area divided into 24 plots with six treatments and four replicates (Nitrogen (N); Leucaena (L); Nitrogen+Leucaena (N+L); Humic Acid+Leucaena (HA+L); Humic Acid+Nitrogen (HA+N) and Humic Acid+Nitrogen+Leucaena (HA+N+L)). Each plot was cropped with maize (Zea mays L.) and the grains yield was estimated. Soil samples were collected at depths of 0–5 cm, 5–10 cm and 10–20 cm. Potential acidity, pH, soil organic carbon (SOC), available phosphorus, exchangeable potassium, calcium and magnesium, cation exchange capacity (CEC), sum of basic cations (SBC) and base saturation (BS) were determined. Principal component analysis (PCA) was used to correlate soil chemical attributes with maize yield. Calcium, magnesium, available P and SBC were related to the maize grains yield in upper soil layer, especially at nitrogen fertilization. This research confirms the hypothesis that there is a linkage between different soil fertilization regimes, soil properties and the maize grains yield.